The role of identity in Turkey’s new Middle East policy: The case of JDP’s Palestine policy - Yetim, Hüsna Taş (İstanbul Sabahattin Zaim Üniversitesi, Sosyal Bilimler Enstitüsü, 2013)
Particularly with the advent of the Justice and Development Party (hereafter JDP), Turkey’s Middle East policy, has transformed into a more assertive and active policy orientation vis-a-vis the 1990s. This new Middle East policy is more assertive and active, and thus seeks to become an important player in the region. Since 2002, Turkey has involved in a number of mediation efforts for possible settlement of the conflicts such as the Palestine-Israeli issue. Moreover, Turkey actively participated in the Arab League Conferences and has established closer ties with the countries in the region such as Syria, Iran, and Iraq. From the outset, some circles have evaluated this new policy just as a result of Islamic oriented policies of the ruling party. On the contrary, this article claims that this new policy towards the Middle East cannot be merely explained by the Islamic-identity of JDP. Main argument of this essay is, unlike Islamic identity, liberal norms are playing gradually increasing role in regional politics particularly in the Palestine Question. In this context, the paper claims that visible changes in Turkey’s foreign policy can be explained comprehensively by using some tools of constructivist IR theory, such as the identity-led politics.
Keywords: constructivism; Middle East Policy; Turkish Foreign Policy; Konstruktivism; Ortadoğu politikaları; Filistin; Türk dış politikası